Analysis of High School Students’ Learning Difficulties in Understanding the Mechanics Concept - Wulandari, Wahyu Nur; Wiwith Eskha Ardhanariswari; Khalidah, Hanin Izzatul; Setiaji, Bayu (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2021)
Students have difficulty learning to understand the concept of mechanics. This is due to not having mastered the prerequisite skills. This study aims to determine the difficulties of students in understanding and mastering mechanical material. This study uses a descriptive method with quantitative and qualitative approaches. The subjects of this study were 18 high school students, both private and public in Yogyakarta, which were taken using a stratified random sampling technique. The steps of this research include finding references, determining subjects, making questionnaires, distributing questionnaires, analyzing data, and concluding. The instrument used is a questionnaire with answers that can be in the form of choices, opinions, and/or suggestions. The results of the study show that most students considered physics to be a difficult subject, especially the concept of mechanics. The concepts of mechanics that are considered difficult are rotational dynamics and rigid body equilibrium; impulse, momentum, the law of conservation of energy, and fluid dynamics. The learning method applied by the teacher is not appropriate because it only provides material without a more complete explanation. Students have difficulty physics learning on mechanics material because of their perception and inappropriate learning methods.